2018
DOI: 10.1177/2474126418815823
|View full text |Cite
|
Sign up to set email alerts
|

Worsening Proteinuria Following Intravitreal Anti-VEGF Therapy for Diabetic Macular Edema

Abstract: Intravitreal antivascular endothelial growth factor (anti-VEGF) therapy is a standard of care for a variety of ophthalmological conditions. While the systemic use of these agents in oncology is well known to induce a number of renal-related adverse effects such as worsening hypertension and proteinuria, the ability of local intravitreal injections to cause similar side effects has traditionally been thought to be unlikely given the lower doses used. In this case report, we describe an 88-year-old woman who dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…21 The most recent study by Kenworthy et al reports worsening of chronic stable proteinuria that was attributed to diabetic nephropathy after intravitreal injection of bevacizumab. 70 A recent retrospective study of 69 patients did not report acute kidney injury after a short-term follow-up of 7 to 30 days after intravitreal injections of bevacizumab, aflibercept, or ranibizumab. 71 Levels of anti-VEGF agents and proteinuria were not monitored.…”
Section: Intravitreal Anti-vegf Administration: Systemic Absorptionmentioning
confidence: 99%
“…21 The most recent study by Kenworthy et al reports worsening of chronic stable proteinuria that was attributed to diabetic nephropathy after intravitreal injection of bevacizumab. 70 A recent retrospective study of 69 patients did not report acute kidney injury after a short-term follow-up of 7 to 30 days after intravitreal injections of bevacizumab, aflibercept, or ranibizumab. 71 Levels of anti-VEGF agents and proteinuria were not monitored.…”
Section: Intravitreal Anti-vegf Administration: Systemic Absorptionmentioning
confidence: 99%
“…There are three more in this case series and one more under review. In total, there are 30 known cases demonstrating systemic toxicity after intravitreal VEGF inhibitor injections (2,4,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). See Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Other TMA presentations after intravitreal VEGF blockade in the literature are reviewed in Table 1 (4,32,39,42,43,46) along with other published evidence (2,4,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Other glomerular lesions such as collapsing glomerulopathy have been associated with intravitreal anti-VEGF agents as well (2,4).…”
Section: Discussionmentioning
confidence: 99%
“…24 Our literature review revealed 26 cases of severe renal injuries after intravitreal anti-VEGF injections that required nephrological management (Table 1). [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] These cases were reported in 2011-2021, 69% were male, 81% were older than 50 years and DR/DME was the most common indication (62%) followed by nAMD (27%). Most received bevacizumab alone (58%) or followed by either ranibizumab and/or aflibercept (23%).…”
Section: Case Reportmentioning
confidence: 99%